PENEGAKAN HUKUM TERHADAP PELAKU USAHA PEMBUATAN TANDA NOMOR KENDARAAN BERMOTOR TIDAK RESMI DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Jonatan Alexander G; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The motorized vehicle number mark is proof of the legitimacy of operating a motorized vehicle in the form of a license plate or other material with certain specifications issued by the Indonesian National Police and containing the area code, registration number, and validity period and installed on the vehicle. So, the motor vehicle number sign is other than that. declared invalid and invalid. A motorized vehicle number sign is a must for every motorized vehicle user when owning a motorized vehicle. However, in fact, many motorists use unofficial Motor Vehicle Number Marks made on business actors to produce unofficial Motor Vehicle Number Signs in Pekanbaru city. which should have been in Article 62 in conjunction with Article 8 Paragraph (1) Sub-Paragraph (a) of Law Number 8 Year 1999 concerning Consumer Protection, business actors may be subject to a maximum imprisonment of five years or a maximum fine of Rp. 2 billion. However, until now, law enforcement against business actors making unofficial Motor Vehicle Numbers in Pekanbaru has never been enforced.This type of research is classified as legal sociological research because in this study the author directly conducts research at the location or place to provide a complete and clear picture of the problem under study. This research was conducted at the Pekanbaru City Police and Pekanbaru City Police. While the population and sample are all parties related to the problems studied in this study, the data sources used are primary data, secondary data and tertiary data. Data collection techniques in this study were carried out by interviews, questionnaires and literature study.This study aims to find out how law enforcement against business actors making unofficial Motor Vehicle Numbers in the jurisdiction of the Pekanbaru City Police, what obstacles are faced in law enforcement against business actors making unofficial Motor Vehicle Numbers in the jurisdiction of the Pekanbaru City Police. , as well as what efforts can be made to overcome obstacles in law enforcement against business actors producing unofficial Motor Vehicle Numbers in the jurisdiction of the Pekanbaru City Police.Keywords: Law Enforcement, Business Actors Making Number Plates, Special Crime